The Story of Film : The Hollywood Dream (Kanopy, ,, 2016)
This is the fascinating story of the movies in the roaring 20s. We see how Hollywood became a glittering entertainment industry and how star directors like Charlie Chaplin and Buster Keaton emerged. But the gloss and fantasy was challenged by movie makers like Robert Flaherty, Eric Von Stroheim and Carl Theodor Dreyer, who wanted films to be more serious and mature. Filmed in Hollywood, Denmark and Moscow, this part looks at the battle over the soul of cinema and some of the greatest movies ever made..

Zombie Girl - Making Horror Film (Kanopy, ,, 2009)
Emily Hagis is filming her first feature film. She wrote the screenplay, and will be directing it herself. The zombies shuffle, and there's plenty of blood. The big difference is that Emily is twelve. This funny, tender documentary follows Emily and her family on her first feature film. This film is a fascinating look at a growing world of young movie makers, and the bloodiest mother/daughter movie you've ever seen!. Slamdance Film Festival 2009 - Winner Spirit of Slamdance Award.

The Story of Film : The Golden Age of World Cinema (Kanopy, ,, 2016)
The 1920s were a golden age for world cinema. In this part, we visit Paris, Berlin, Moscow, Shanghai and Tokyo to discover the places where movie makers were pushing the boundaries of the medium. German Expressionism, Soviet montage, French impressionism and surrealism were passionate new film movements, but less well known are the glories of Chinese and Japanese films and the moving story of one of the great, now forgotten, movie stars: Ruan Lingyu..

In darkest Hollywood (Kanopy, ,, 2014)
Almost from the beginning of cinema, filmmakers have looked at the continent of Africa with a mixture of fear and fascination, prejudice and contempt. South Africa, with its fabulous mineral wealth, exotic locations, and white settlers, attracted scores of movie makers. Now, when the era of white rule has ended, In darkest Hollywood asks: What was the role of cinema during the 45 year reign of apartheid? Through a mosaic of feature, documentary, and propaganda films, with commentary by writers, directors, and actors, some of whom supported apartheid, and others who fought to destroy it, In darkest Hollywood turns the lens towards the filmmakers and the society they so often misunderstood and misrepresented. This two-part series examines the role of cinema in both supporting and attacking apartheid. It questions Hollywood's commitment to racial stereo types and reluctance to depict black heroes. Among those appearing are: Lewis Nkosi, Zakes Mokae, Sir Richard Attenborough, Lonel Rogosin, Thomas Mogotlane, Andre Brink, Euzhan Palcy. First Prize, Big Muddy Film FestivalGold Plaque Award, Chicago International Film Festival; London Film Festival; Berlin Film Festival; Amsterdam Film Festival. Directed by: Peter Davis Daniel Riesenfeld.

Lavender limelight (Kanopy, ,, 2014)
From Go fish to Paris is burning to The watermelon woman, this festival favorite goes behind the scenes to reveal seven successful lesbian directors. These talented movie-makers enlighten and entertain as they explore their sexual identity, growing up gay, inspirations and techniques, Hollywood vs. Indie, and of course, love and sex, onscreen and off. The conversations are intimate, the topics unlimited, and the clips from their work enthralling! Featuring Cheryl Dunye, Rose Troche, Jennie Livingston, Monika Treut, Maria Maggenti, Su Friedrich and Heather MacDonald. Enthralling and intimate!" - OutFest LA. "Inspirational and funny ... A must-see!" - San Francisco International Lesbian & Gay Film Festival. "This award-winning documentary provides wonderful insight into the inspirations, aspirations and major aesthetic and content-based concerns of seven groundbreaking lesbian filmmakers. Featuring interviews as well as carefully chosen clips from each of its subjects' films, Lavender limelight is an outstanding introduction to the work of our finest queer auteurs. A must-have for the lesbian cinephile." - Candace Moore, Curve Magazine.

Miranda July: An Interview (Kanopy, ,, 2015)
Miranda July (b.1974) makes performances, movies, and recordings""often in combination. Her videos (The Amateurist, Nest of Tens, Getting Stronger Every Day) present complicated parallel narratives with characters who experience loneliness, exploitation, unexpected phobias, and often inexplicable relationships. July has also recorded several performance albums released by Kill Rock Stars and K Records. In 1995 she founded Joanie 4 Jackie, an on-going movie distribution network for independent women movie makers. In this interview, July descibes how an imprisoned convict inspired her to write her first play at the age of 14. This overwhelming emotional receptiveness and compassion for others has continued to drive July's work. She goes on to discuss the use of personal metaphor and symbolism in her work, and how she displaces them in order to conceal her exact proximity to the subject. July describes her desire to go beyond simple empathy in order to have her references exist as pure emotion that the viewer will be able to graft onto their own stories. The artist concludes by discussing her upcoming projects, including her attempt to do flyering for the 2002 Whitney Biennial, and her 2005 feature film Me and You and Everyone We Know. -- Kyle Riley Interview conducted Dara Greenwald and Blithe Riley in February 2002, edited in 2014.

The Celluloid Bordello (Kanopy, ,, 2022)
Since the dawn of cinema, sex workers have served as muses to movie-makers. From turn of the century white slavery pictures (The Girl who went Astray, 1900), to iconic rom-coms (Pretty Woman, 1990), to indie hits (Tangerine, 2015), hookers, hustlers, call girls, street walkers, strippers and dommes have been staples of the silver screen. Cinematic sex workers are punchlines, cautionary tales or fantasy figures. They are brutalized, killed off, sometimes rescued and almost always represented as if no sex worker is in theater. Even in documentary films such as Born Into Brothels (2004) or Tricked (2013), reality is distorted by filmmakers (almost always non-sex workers), who are determined to show trauma, violence and pathos rather than the resilience, successes, and thriving communities that are the norm for many sex workers. THE CELLULOID BORDELLO brings sex workers to the theater. With equal parts historical overview, critique, and homage, the film lets real life dommes, escorts, porn stars and hustlers tell you which films they love and which they hate, which get it right and which miss the mark and, most importantly, how perpetuating stereotypes in media affects real peoples' lives.

Unseen cinema: early American avant-garde film 1894-1941 (Kanopy, ,, 2018)
UNSEEN CINEMA: EARLY AMERICAN AVANT-GARDE FILM 1894-1941 is the ground-breaking retrospective that explores long-forgotten American experimental films made in the United States and Europe during the formative period of cinema. Arranged into thematic programs, the digital version consists of over 140 films, newly preserved and restored in 35mm and 16mm film prints. The series postulates an innovative and often controversial view of experimental cinema as a product of avant-garde artists, of Hollywood directors, and of amateur movie-makers working collectively and as individuals at all levels of film production during the last decade of the 19th century and the first half of the 20th century. Anthology Film Archives and Deutsches Filmmuseum working in collaboration with 60 of the world's leading film archive collections including British Film Institute, George Eastman House, Library of Congress, and Museum of Modern Art, among many others, prepared preservation and restorations masters of the rare art films. Many of the films have not been available since their creation over a century ago, some have never been screened in public, and almost all have been unavailable in pristine projection prints until now. The films have been seen at museums, archives, universities, and theaters around the world. Over 500 venues have featured the UNSEEN CINEMA, making it one of the largest and perhaps the most viewed film retrospectives in history.

Years of living dangerously: Season 1 (Showtime Networks Inc, 2014)
"This groundbreaking documentary event series explores the human impact of climate change. From the damage wrought by Hurricane Sandy to the upheaval caused by drought in the Middle East, YEARS OF LIVING DANGEROUSLY combines the blockbuster storytelling styles of top Hollywood movie makers with the reporting expertise of Hollywood's brightest stars and today's most respected journalists"--Showtime website.
Disc 1. Dry seasons (58 min.) ; End of the woods (57 min.) , Disc 2. The surge (53 min.) ; Ice & brimstone (58 min.) , Disc 3. True colors (58 min.) ; Winds of change (58 min.) , Disc 4. Revolt, rebuild, renew (55 min.) ; A dangerous future (58 min.) , Disc 5. Moving a mountain (58 min.).